Seasonal Variations and Long-term Trend of Mineral Dust Aerosols over the Taiwan Region - Yanda Zhang; Yi-Jhen Cai; Fangqun Yu; Gan Luo; Charles C. K. Chou (Aerosol and Air Quality Research)
Abstract Atmospheric dust aerosols are known to affect the air quality and public health as well as climate and weather systems. An increasing number of modeling studies have related ice nucleation with the number concentrations of dust particles with a diameter larger than 500 nm (ND,d>500nm). In this paper, the seasonal variation, vertical properties, and long-term trend of ND,d>500nm over the Taiwan region are analyzed, using simulations from a global chemical transport model with size-resolved particle microphysics. Over Taiwan, ND,d>500nm shows a bimodal seasonal variation distribution with two peaks in spring (March–May) and fall-early winter (October–December). In the different seasons, ND,d>500nm varies by about one order of magnitude from summer to spring (0.06–1.23 cm−3 in the boundary layer, 0.03–0.55 cm−3 in the middle and lower troposphere, and 0.006–0.03 cm−3 in the upper level). Vertically, ND,d>500nm profiles show the unimodal distribution, with the highest ND,d>500nm appears at ~1 km and decreasing with altitude. From surface to high levels, the frequencies of intense dust events decrease in fall (September–November) and increase in summer months (June–August). The long-term model results suggest a decreasing trend of the strong dust event frequencies and annual mean ND,d>500nm over Taiwan in the last two decades. From 1999 to 2018, the number of strong dust event days and ND,d>500nm decreased by 40–43% and 37–54%, respectively, under 4 km, and the decline is weaker at higher altitudes. The analysis suggests that these decrease trends are caused by the declining Asian dust emissions.